Epidemiologic profiles of subclinical rheumatic heart disease in children - Dewi Rahmawati Syam; Deny Salverra Yosy; Achirul Bakri; Ria Nova (Indonesian Pediatric Society, 2020)
Background Rheumatic heart disease (RHD) causes premature deaths every year worldwide. Low socioeconomic level is considered to be a risk factor facilitating the transmission of airway infections due to Streptococcus pyogenes. Subclinical RHD is a stage of RHD in which heart valve abnormalities have occurred according to the WHO or WHF classification but without any complaints to the subject. Echocardiography is used to screen subclinical RHD in several countries. Objective To estimate the prevalence, risk factors, and echocardiographic features of subclinical RHD in children. Methods This cross-sectional study was conducted on 250 elementary school children in Palembang, South Sumatera. We interviewed subject's parents about family characteristics, environment, and history of recurrent sore throat. Subjects underwent anthropometric examination, auscultation, and echocardiography. Diagnosis of RHD was based on World Health Organization (WHO) and World Heart Federation (WHF) criteria. Results Of 250 subjects, 132 (53.8%) were girls. Subjects’ age range was 5-14 years. The prevalence of subclinical RHD was 8% (95%CI 4.8 to 11.6). Of the 20 subclinical RHD subjects, 15 (75%) met the possible RHD criteria, 5 (25%) met the probable RHD criteria, and none met the definite RHD criteria. Multivariate analysis showed that household crowding (OR 8.135; 95%CI 1.048 TO 63.143; P=0.045), history of recurrent sore throat within the previous 6 months (OR 6,476; 95%CI 1.79 to 23.427; P=0.004) and age > 10 years (OR 3.167, 95%CI 1.184 to 8.471; P=0.022) significantly increased the risk of subclinical RHD. Conclusion The prevalence of subclinical RHD in elementary school children in Palembang was 8%. For echocardiographic features, most cases met the WHO/WHF possible RHD criteria. Factors significantly associated with the incidence of subclinical RHD are age > 10 years, household crowding, and history of recurrent sore throat in the previous 6 months.